2019
DOI: 10.21037/atm.2019.07.26
|View full text |Cite
|
Sign up to set email alerts
|

Banxia Xiexin decoction, a traditional Chinese medicine, alleviates colon cancer in nude mice

Abstract: Backgrounds: Banxia Xiexin decoction (BXD) is widely used in the treatment of acute and chronic gastritis, peptic ulcer, dyspepsia, gastrointestinal dysfunction, chronic hepatitis, oral ulcer and other diseases, but there are few reports on its treatment of colon cancer. The current study was designed to investigate the effect of BXD on colon cancer and its possible molecular mechanisms.Methods: Fifty SPF BALB/c nude mice were selected to establish an animal model of colon cancer bearing nude mice. Establishme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The Banxia Xiexin Decoction (BXD), one of its active components being rhein, is prescribed to ease various inflammatory disorders like gastritis and upper airway inflammation [78]. The BXD was also effective in curing colon cancer in animals [79].…”
Section: Ethnopharmacological Uses Of Plants Containing Rheinmentioning
confidence: 99%
See 2 more Smart Citations
“…The Banxia Xiexin Decoction (BXD), one of its active components being rhein, is prescribed to ease various inflammatory disorders like gastritis and upper airway inflammation [78]. The BXD was also effective in curing colon cancer in animals [79].…”
Section: Ethnopharmacological Uses Of Plants Containing Rheinmentioning
confidence: 99%
“…Many biological properties of rhein have been studied, such as curing inflammatory disorders like upper airway inflammation, asthma, gastritis, and fatty liver and protecting against cerebral ischemic injury, diabetic nephropathy, etc. [42,78,79,91,92]. Several studies have shown that rhein is an effective antidiabetic, antiosteoarthritic and anticathartic agent [39,40,44,45,60].…”
Section: Biological Activities Of Rheinmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally in China, 5-fluorouracil (5-Fu) alone or in combination with other anticancer agents (such as irinotecan or oxaliplatin) has been frequently administered and has been shown to improve the survival rate of patients with partial colon cancer ( 5 , 6 ). In addition, the anticarcinogenic effect of several traditional Chinese medicines has also been emphasized in colon cancer ( 7 , 8 ). The authors' previous study demonstrated that modified Si-Jun-Zi Decoction (SJZ), a Chinese medicinal formula, could inhibit colon cancer liver metastasis by increasing the content of macrophage cells ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM), with ancient application history in China or other regions of Asia, has gained considerable importance in defending against cancer during the last two decades [13][14][15]. Blood stasis, characterized by blood flow retardation and blood stagnation [16][17][18], is an essential factor for tumor metastasis during tumorigenesis in the TCM basic theory system [19,20].…”
Section: Introductionmentioning
confidence: 99%